A Gene-based restoration of Akt activity in endothelial progenitor cells from human subjects at high cardiovascular risk rescues vascular reparative capacity. (16th May 2012) - Cubbon, R M; Viswambharan, H; Baliga, V; Yuldasheva, N; Stephen, S; Askham, J; Mercer, B N; Rakobowchuk, M R; Sukumar, P; Skromna, A; Li, J; Ponnambalam, S; et al.
Abstract : Introduction: Late-outgrowth endothelial progenitor cells (LEPC) are putative mediators of endogenous vascular repair, and represent an attractive tool for future cell-based cardiovascular repair strategies. However, progenitor function may be impaired in high cardiovascular risk populations, such as those of South Asian (SA) ethnicity, in whom cell based therapies are likely to offer most benefit. Methods: Detailed analysis of in vitro LEPC function (abundance, proliferation, migration, angiogenesis and senescence) was performed in 12 SA men and 12 matched White European (WE) controls. Molecular abnormalities within the Akt/eNOS signalling axis were analysed with PCR and western blotting. LEPC were transfused into immunodeficient mice subsequent to femoral artery injury to assess in vivo reparative function. In vitro and in vivo studies were repeated after lentiviral gene delivery of constitutively active Akt1 (E17K) or control (EGFP) to SA LEPC; augmented Akt activity was confirmed using a Glycogen Synthase Kinase phosphorylation assay. Data are expressed as mean [SEM] and compared with t tests as appropriate; statistical significance is defined as p<0.05 (denoted by *). Results: The two groups were matched for age and cardiovascular risk factors, although the SA group was comparatively insulin resistant (HOMA-IR 1.2 [0.2] vs 0.5 [0.1] au*). SA LEPC exhibited impaired colony formation (0.06 [0.02] vs 0.19 [0.03] colonies/ml blood*), migration to vascular endothelial growth factor (5 [0.7] vs 10 [1.7] cells/microscopic field*) and in vitro angiogenesis (1.9 [0.6] vs 3.8 [0.5] tubular structures/microscopic field*), associated with markedly decreased abundance of the phosphorylated forms of the pro-angiogenic molecules S473-Akt (0.14 [0.05] vs 0.81 [0.2] au*) and S1177-eNOS (0.05 [0.02] vs 0.15 [0.01] au*). Transfusion of WE LEPC into immunodeficient mice after wire-induced femoral artery luminal injury augmented re-endothelialisation; however, neither SA LEPC, nor vehicle, augmented re-endothelialisation (WE: 54.2 [6.4], SA: 36.9 [3.4], vehicle: 31.1 [2.4] % re-endothelialised; WE vs SA*; SA vs vehicle p=0.2). Lentiviral gene delivery of a E17K, but not EGFP control, to SA LEPC was associated with augmented Akt1 activity and rescue of in vivo re-endothelialisation capacity (E17K: 55.2 [4.4] vs EGFP 24.1 [1.3] % re-endothelialised; E17K vs EGFP*; E17K vs WE non-transduced cells p=0.9). Conclusions: These data provide proof of principle for human LEPC based vascular repair therapy, and demonstrate a mechanism by which to rescue marked progenitor dysfunction in a group at high risk of cardiovascular events, whom are likely to benefit from cardiovascular repair therapies.